OPTIMALISASI PERAN PEMERINTAH DAERAH DALAM PERLINDUNGAN HUKUM TERHADAP BERAS BERDASARKAN KONSEP KEDAULATAN PANGAN DI INDONESIA - M. Rendi Aridhayandi (Jurnal Hukum Mimbar Justitia, 2019)
As a staple food in Indonesia, the availability of rice are needed to continue until whenever. Because agriculture is still the source of livelihood of the majority of the workforce in Indonesia. Hence the presence of the government is necessary, governments can differentiate into central government and local governments. In UUD 1945 Pasal 18A ayat (1) mentions the relationship of authority between the central government and provincial government, counties, and cities, or between provinces and districts and cities, regulated by law with due regard to the specificity and diversity of the area. Regional autonomy is one manifestation of freedom for the regions to be involved in designing the activity of politics and government at the local level in order to strengthen the power of national government. Thus the role of local government is very important to the affairs of the availability of rice in the presence of local autonomy. The local government and regional autonomy can be free to design a territory in support of the central government towards food security.Undang-Undang No. 18 tahun 2012 tentang Pangan mentions the issue of food intended to achieve three things at once, namely food sovereignty, food self-sufficiency and food security. President Jokowi that: "Food security is distinct from food sovereignty. Food security is simply the availability of foodstuffs (logistics) in the warehouse and on the market irrespective of origin whether imported or locally produced. Food sovereignty means that we manufacture and market our own groceries, while surplus production is exported ". Here we can see that food sovereignty is significantly deeper than food security. thus, the optimization of local governments in order to achieve food sovereignty can be: 1. the agrarian reform (land protection by performing a spatial planning regulations); 2. the legal protection to farmers (by making regulations that aim the welfare of farmers); 3. the availability of seeds, fertilizers and tools supporting production; 4. Registering brands and geographical indications of agricultural products to the Directorate General of Intellectual Property Ministry of law and Human Rights Republic of Indonesia; 5. setting the price, product quality and market share of an agricultural product.Â Keywords: Food Security; Food Sovereignty; Rice; Regional Government.